2016
DOI: 10.1051/0004-6361/201628106
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution abundance analysis of red giants in the metal-poor bulge globular cluster HP 1

Abstract: Context. The globular cluster HP 1 is projected at only 3 • .33 from the Galactic center. Together with its distance, this makes it one of the most central globular clusters in the Milky Way. It has a blue horizontal branch (BHB) and a metallicity of [Fe/H] ≈ −1.0. This means that it probably is one of the oldest objects in the Galaxy. Abundance ratios can reveal the nucleosynthesis pattern of the first stars as well as the early chemical enrichment and early formation of stellar populations. Aims. High-resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(86 citation statements)
references
References 88 publications
9
76
0
1
Order By: Relevance
“…The radial velocity of this probable HP1 star is 42.25±2.75 km s −1 . This value is in agreement with that computed by Barbuy et al (2016). The axisymmetric Galactic model includes a Sérsic bulge, an exponential disc generated by the superposition of three Miyamoto-Nagai potentials (Miyamoto & Nagai 1975), following the methodology made by Smith et al (2015), and a dark matter halo is modelled with the Navarro-Frenk-White (NFW) density profile (Navarro et al 1997), having a circular velocity V 0 = 241 km s −1 at R 0 = 8.2 kpc (Bland-Hawthorn & Gerhard 2016).…”
Section: Orbital Analysis Of Hpsupporting
confidence: 93%
See 1 more Smart Citation
“…The radial velocity of this probable HP1 star is 42.25±2.75 km s −1 . This value is in agreement with that computed by Barbuy et al (2016). The axisymmetric Galactic model includes a Sérsic bulge, an exponential disc generated by the superposition of three Miyamoto-Nagai potentials (Miyamoto & Nagai 1975), following the methodology made by Smith et al (2015), and a dark matter halo is modelled with the Navarro-Frenk-White (NFW) density profile (Navarro et al 1997), having a circular velocity V 0 = 241 km s −1 at R 0 = 8.2 kpc (Bland-Hawthorn & Gerhard 2016).…”
Section: Orbital Analysis Of Hpsupporting
confidence: 93%
“…CMDs. Interpolations in metallicity were performed in order to compute isochrones with −1.26 ≤ [Fe/H] ≤ −0.86 in steps of 0.02 dex, therefore fully covering the accurate value of [Fe/H]= −1.06 ± 0.10 from high-resolution spectroscopic analysis of Barbuy et al (2016).…”
Section: Stellar Evolutionary Modelsmentioning
confidence: 99%
“…Moreover, our finding show good compatibility with the result of Barbuy et al (2016), they concluded that abundances of HP1 agree with enrichment by SNII at early epoch, our result show a good agreement with enrichment by SNIa, which happen later. These results are indication that NGC6528 is younger that HP1, which would be expected by its metallicity.…”
Section: Iron-peak Elementssupporting
confidence: 88%
“…In the present work we analyse individual stars in the reference globular cluster 47 Tucanae ([Fe/H] 1 = −0.67, Alves-Brito et al 2005), and the bulge globular clusters NGC 6553 ([Fe/H] = −0.20, Alves-Brito et al 2006), NGC 6528 ([Fe/H] = −0.11, Zoccali et al 2004), NGC 6522 ([Fe/H] = −0.95, , HP 1 ([Fe/H] = −1.00, Barbuy et al 2006Barbuy et al , 2016, and NGC 6558 ([Fe/H] = −1.00, Barbuy et al 2017). In previous work we have derived the abundances of the α-elements (O, Mg, Ca, Si, Ti), odd-Z (Na, Al), s-process (Ba, La, Zr), and r-process 1 We adopted here the usual spectroscopic notation that [A/B] = log(NA/NB) − log(NA/NB) and (A) = log(NA/NB) + 12 for each elements A and B.…”
Section: Introductionmentioning
confidence: 99%